CircEZH2E2/E3 is a dual suppressor of miR363/miR708 to promote EZH2 expression and prostate cancer progression. Issue 4 (28th December 2022) - Su, Zhengzheng; Zhang, Mengni; Luo, Han; Zhong, Jinjing; Tan, Junya; Xu, Yunyi; Pan, Xiuyi; Zeng, Hao; Nie, Ling; Xu, Miao; Chen, Ni; Chen, Xueqin; et al.
Abstract: The histone methyltransferase enhancer of zeste homolog 2 (EZH2) is overexpressed in a variety of malignancies including prostate cancer (PCa) and may play important roles in tumor progression. Gene copy number gains, enhanced transcription, and a few circRNAs have been reported to upregulate EZH2. It was not known whether EZH2 itself generates circRNAs that promote its own expression. We here report the identification of circEZH2 E2/E3 that is derived from exons 2 and 3 of the EZH2 gene and overexpressed in PCa. We show that circEZH2 E2/E3 functions as a dual inhibitor for both miR363 and miR708 that target the EZH2 3′UTR and CDS, respectively, resulting in the upregulation of EZH2 expression and hence the downregulation of EZH2‐repressed genes (e.g., CDH1 and DAB2IP ), and enhancement of PCa cell proliferation, migration, invasion, and xenograft PCa growth. Overexpression of circEZH2 E2/E3 is significantly correlated with higher tumor grade, tumor progression, and unfavorable progression‐free and disease‐specific survival in PCa patients. These findings show a novel autoenhancing EZH2–circEZH2 E2/E3 ‐miR363/miR708–EZH2 regulatory loop, by which circEZH2 E2/E3 plays important roles in PCa tumorigenesis and progression by upregulating EZH2, and may have potential diagnostic, prognostic, and therapeutic uses in PCa management. Abstract : The EZH2‐derived circEZH2 E2/E3 functions as a dual suppressor of both miR363 and miR708 by competitively binding to miRNAs and blocking their inhibitory effects on EZH2 expression, resulting in EZH2 overexpression, which in turn inhibits transcription of downstream tumor‐suppressive genes such as E‐cadherin and DAB2IP and promotes prostate cancer cell growth and tumor progression.